Strategi Peningkatan Kualitas Rujak Kuah Pindang Di Warung D’Abian Kelan - Kurniawati, Ni Kadek Gita; Hartiati, Amna; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
Quality improvement in pindang sauce salad is the focus of research to get the right strategy as an effort to improve the process of making pindang sauce salad so that it can meet consumer satisfaction. Pindang sauce salad is a food that comes from a mixture of several fresh fruits using spices including fish broth and seasonings. The purpose of this study is to determine the quality attributes of products that are considered important to consumers of pindang sauce salad products, analyze the priority of improvement of pindang sauce salad products and determine the right strategy to improve the quality of pindang sauce salad products. The research method used is quality function deployment, using qualitative and quantitative data through observation and survey methods. The results obtained quality attributes that are considered important by consumers are the quality of pindang sauce, fruit quality, salad flavor, appearance, price, portion, durability, quality of shrimp paste. Prioritizing the improvement of the quality of pindang sauce salad in D'Abian Kelan shop is on the quality attribute of shrimp paste with the highest improvement ratio of (1.121), price attributes (1.119), and durability attributes (1.116). The strategy to improve the quality of pindang sauce salad at the D'Abian Kelan shop is to evaluate the technical parameters that have the highest priority for improvement based on the value of the level of technical importance, namely the technical parameters of raw material preparation, portioning of raw materials and making pindang sauce.